Processing of NAA and NAAG edited spectra acquired using the MEGA-PRESS sequence - Landim , Ricardo C. G.; Edden , Richard A. E.; Foerster , Bernd; Li , Li M.; Covolan , Roberto J. M.; Castellano , Gabriela (Physicae Proceedings, 2012)
In the present work we used a MEGA-PRESS sequence to separately measure the contributions of NAA and NAAG in human brain spectra during a functional experiment using visual stimulation. The paradigm used consisted of one off block of 5min20s followed by an on block and another off block, both with 10min40s, tested on 8 healthy subjects. Visual stimuli consisted of a radial black-white checkerboard flickering at 8 Hz. Because resulting NAA/NAAG peaks at 2.5ppm are small and have undefined shapes, the pre-processing and quantification steps are complex. The phase and frequency corrections seemed to work for some spectra within a scan but not for all, and therefore a possible solution might be to perform case-to-case corrections. Averaging spectra over subjects seemed to give an acceptable SNR for the NAA experiment, but not for the NAAG experiment, for which the 2ppm residue stayed as visible as the peak of interest at 2.5ppm. Specific frequency corrections for this experiment have to be investigated more thoroughly. Quantification with AMARES resulted in large quantification errors, which did not allow assessment of possible stimulus-associated changes. These errors were expected due to the undefined shape problem.